[Fe(CN)6] vacancy-boosting oxygen evolution activity of Co-based Prussian blue analogues for hybrid sodium-air battery. (June 2021) - Kang, Y.; Wang, S.; Hui, K.S.; Li, H.-F.; Liang, F.; Wu, X.-L.; Zhang, Q.; Zhou, W.; Chen, L.; Chen, F.; Hui, K.N.
Abstract: Prussian blue analogues (PBAs) have emerged as efficient catalysts for oxygen evolution reaction (OER) due to their porous structure with well-dispersed active sites. However, Co-based PBA (Co-PBA) electrocatalysts are characterized by moderate OER kinetics. In this study, we developed a facile high-yield strategy to fabricate defective Co-PBA (D-Co-PBA) with [Fe(CN)6 ] vacancies and exposed Co (III) active sites by post-oxidation treatment of the pristine Co-PBA with aqueous H2 O2 . Rietveld refinement results show that the lattice parameter (a) and unit-cell volume (V) of D-Co-PBA are smaller than those of the pristine Co-PBA, thereby confirming the generation of [Fe(CN)6 ] vacancies. Density functional theory calculations reveal that the [Fe(CN)6 ] vacancy can effectively regulate the electronic structure of D-Co-PBA; this condition reduces the reaction barrier of the rate-determining step toward OER. In OER, the D-Co-PBA catalyst achieves a lower overpotential of 400 mV at a current density of 10 mA cm −2, which is superior to that of Ir/C (430 mV) and Co-PBA (450 mV). A hybrid sodium–air battery assembled with Pt/C and D-Co-PBA catalysts displays a discharge voltage of 2.75 V, an ultralow charging–discharging gap of 0.15 V, and a round-trip efficiency of 94.83% on the 1000th cycle at the current density of 0.01 mA cm −2 . This study is highly promising for large-scale production of affordable and effective PBA-based materials with desirable OER activity for metal-air batteries and water-alkali electrolyzers, thus helping achieve the goal of sustainability. Graphical abstract: Image 1 Highlights: Defective Co Prussian blue analogue (D-Co-PBA) by breaking bonds of iron carbon-nitrogen-cobalt units was synthesized. Exposing Co (III) active sites in D-Co-PBA, the catalyst shows a remarkable OER performance. DFT calculations suggest the electronic structure of D-Co-PBA can be tuned by introducing [Fe(CN)6 ] vacancy defects. A hybrid sodium-air battery displays a low charging-discharging gap of 0.15 V and high stability up to 1000 cycles.